Monuments of barbarism: memory spaces and their forgotten remembrances (Research, Society and Development, 2022)
This article seeks, from a literature review of authors such as Sigmund Freud, Pierre Nora and, in particular, Walter Benjamin, to analyze the constant presence of historical monuments in the lives of a not inconsiderable part of the population. In order to do so, the monuments in question will be seen as places of memory, that is, as spaces in which the remembrances of a certain social sphere were consigned. From the aforementioned way of seeing the palaces, obelisks, squares and other monuments, the text seeks to demonstrate that they end up representing a largely excluding history, which disregards numerous groups of paramount importance to the social environment. As an example of the approach developed, the article analyzes the city of Petrópolis, often seen as “the only imperial city in the Americas” and/or as “the city of the German colonist”, both distorted views that end up excluding from the rich history of the place the other groups (Italian and Portuguese immigrants and, specifically, the enslaved blacks, among others) that participated in the construction of the city.